No time to die [videorecording (Blu-Ray)] - Fukunaga, Cary Joji, 1977-; Purvis, Neal; Wade, Robert, 1961-; Waller-Bridge, Phoebe, 1985-; Craig, Daniel, 1968-; Malek, Rami; Seydoux, Léa, 1985-; Lynch, Lashana, 1987-; Whishaw, Ben, 1980-; Harris, Naomie, 1976-; Magnussen, Billy, 1985-; Armas, Ana de, 1988-; et al. (SDS, 2021)
Bond has left active service and is enjoying a tranquil life in Jamaica. His peace is short-lived when his old friend Felix Leiter from the CIA turns up asking for help. The mission to rescue a kidnapped scientist turns out to be far more treacherous than expected, leading Bond onto the trail of a mysterious villain armed with dangerous new technology.